Analysis of the nature of economic policy making and management on community (local) economic development, A case of Masha sub county, Isingiro district-Uganda - Namanya, Betrum; Mugabe, Robert (IJRDO - Journal of Business Management, 2017)
The study was about analysisng the nature of economic policy making and management on community economic development. Masha Sub County, Isingiro District in Uganda was used as a case study. The study sought to contribute to the acceleration of community economic development as an everlasting engine for achieving overall economic development of the country. The study used both descriptive and case study research designs. The study used a sample size of 133 respondents. Data was collected using both questionnaire survey and the interview. Data collected was analyzed using descriptive and inferential statistics. Results were presented using frequencies, percentages, mean and standard deviation as well as Pearson product moment correlation index. Results were obtained using SPSS version 17. The findings revealed that the Community is not involved in economic policy making and management. The study concluded that there is a gap in economic policy making and management which has crippled community economic development. This therefore calls for community based planning, popular citizen participation in economic policy making, shared visions in decision making as well as strengthening the capacity of local government institutions to implement and monitor economic development policies.